Description of the females of two species of the genus Lasaia (Lepidoptera: Riodinidae) and new records for Mexico - Arellano-Covarrubias, Arturo; Luis-Martínez, Armando; Llorente-Bousquets, Jorge (Zootaxa, 2023)
Females of two species of the genus Lasaia Bates, 1868, L. arsis Staudinger, [1887] and L. pseudomeris Clench, 1972 are described from specimens deposited in entomological collections. The identity of these species had been uncertain due to scarcity of data, causing misidentifications and confusion in pairing males and females of the same species. Distribution maps for both species, as well as new records of L. arsis for Mexico are provided.